Dune Sand Mortar Effects on Deflections of Repaired Steel Bars-Reinforced Concrete Beams - Djeridane, Madina; Zaidi, Ali; Lakhdari, Mohammed Fatah (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents theoretical and experimental investigations to analyze the flexural behavior of reinforced concrete beams repaired with mortars based on dune sands. The beams supposedly damaged were repaired using mortars based on dune sand varying the mortar cover thickness and the reinforcement ratio. After a suitable cure of beam specimens in the laboratory, they submitted to progressive loading until failure. The results obtained show that the repaired dune sand mortar could be used to enhance the flexural capacity and the ductility of damaged reinforced concrete beams, repaired with dune sand mortars. Comparisons between theoretical and experimental results in terms of deflections are also presented.